Aqueous methanol to formaldehyde and hydrogen on Pd/TiO2 by photocatalysis in direct sunlight: structure dependent activity of nano-Pd and atomic Pt-coated counterparts - Nalajala, Naresh; Salgaonkar, Kranti N.; Chauhan, Inderjeet; Mekala, Siva Prasad; Gopinath, Chinnakonda S. (ACS Applied Energy Materials, 2021)
In the present investigation, facet-controlled Pd nanoparticles with nanocube (Pd-NC) and truncated octahedron (Pd-TO) morphologies, and their counterparts with half-a-monolayer of atomic Pt coated (0.5 theta(Pt)-Pd-NC and 0.5 theta(Pt)-Pd-TO) surfaces were prepared. All of them were characterized and evaluated as cocatalyst after supporting them on commercial titania (P25) (Pd-NC/P25, Pd-TO/P25, 0.5 theta(Pt)-Pd-NC/P25, and 0.5 theta(Pt)-Pd-TO/P25) under direct sunlight and/or one sun conditions for the oxidation of methanol to formaldehyde along with solar hydrogen production. Pd-NC/P25 shows higher activity for hydrogen generation compared to Pd-TO/P25; however, activity reversal occurs with the above cocatalysts, but, after Pt-coating with further enhanced activity. The highest conversion of methanol (0.2 mu mol/h.mg) to 100% selective formaldehyde was observed with 0.5 theta(Pt)-Pd-TO/P25, while other catalysts show significantly lower methanol conversion in the following order: 0.5 theta(Pt)-Pd-TO/P25 > 0.5 theta(Pt)-Pd-NC/P25 > Pd-NC/P25 > Pd-TO/P25. Pt-coated on (111) facets of Pd-TO simulates the activity associated as that of Pt(111) facets and demonstrating the highest and facet dependent activity. The present study is truly in resonance with exploiting the surface properties for heterogeneous catalysis, and highlights that less than a monolayer of Pt is sufficient to simulate the activity as that of bulk Pt. It is worth exploring this concept to other metals and substrates too.
Keywords: heterogeneous catalysis; Nanomaterials; Oxidation; Photocatalysis; surface modification

Baby step in assembling and integrating the components of an artificial photosynthesis device with forced heterojunctions towards improved efficiency - Salgaonkar, Kranti N.; Bajpai, Himanshu; Mhamane, Nitin B.; Nalajala, Naresh; Chauhan, Inderjeet; Thakkar, Kavita; Joshi, Kavita; Gopinath, Chinnakonda S. (Journal of Materials Chemistry A, 2023)
How to achieve unassisted, economical, scalable, and sustainable artificial photosynthesis for liquid fuels/products with improved solar-to-fuel efficiency (STFE) to address a carbon-neutral economy remains a big question. To a large degree, the extent of charge separation at heterojunction interfaces and charge utilization determine the STFE. Towards this, BiVO3 is assembled from ionic-precursors into TiO2 pores, and integrated structurally and electronically with TiO2 on calcination as BiVO4 quantum dots (BVQDs). BVQDs in TiO2 (BVT) pores lead to an all-inorganic system with a sub-quadrillion number of heterojunctions in a 1 cm(2) device (contains similar to 25 mu g of BiVO4 (similar to 2.5 wt%) in the nanopores of similar to 975 mu g of TiO2 (similar to 97.5 wt%)) and facilitate artificial photosynthesis. We demonstrate 31-38% STFE with a photon to chemical conversion turn over frequency (ToF(P2C)) of 2.73 s(-1) with a 1 cm(2) wireless BiVO4-TiO2 artificial leaf (BVT-AL) device for HCHO and CH3OH. The sequential nature of CO2 reduction to HCHO and then to CH3OH is evident from the reaction results. (CO2)-C-13 isotopic labeling experiments confirm that the input CO2 is the source for product formation. A large increase in the photocurrent density and incident photon-to-current efficiency (IPCE) of BVT, over 100% for the BiVO4 photoanode in visible light, demonstrates and supports efficient visible light absorption, charge separation and migration to the redox sites. A device has been demonstrated to show sustainable activity in direct sunlight, and addresses scalability from 1 to 9 cm(2). Assuming no change (50% decrease) in the STFE, a 6.74 m(2) device is expected to convert 1 (0.5) kg h(-1) CO2 into C1-oxygenates in sunlight. DFT calculations carried out with anatase TiO2 (101) and BiVO4 (121) interfaces support many of the experimental findings, including electron flow from the latter to the former, and interaction of the oxygen of TiO2 with BiVO4 and vice versa at the interface towards forced heterojunctions.

Nanostructured Co-doped BiVO4 for efficient and sustainable photoelectrochemical chlorine evolution from simulated sea-water - Chauhan, Inderjeet; Patra, Kshirodra Kumar; Bajpai, Himanshu; Mhamane, Nitin B.; Salgaonkar, Kranti N.; Gopinath, Chinnakonda S. (Dalton Transactions, 2023)
The co-production of hydrogen and chlorine from sea-water splitting could be a potential, sustainable and attractive route by any method. However, challenges to overcome are many, and critically, the sustainability and operating potential of the electrocatalyst are important. In this work, we report on Co-doping in the BiVO4 (Co-BV) crystal lattice and employed the same as the photoanode; Co-BV exhibits a photocurrent of 190 mu A cm(-2) at 1.1 V vs. RHE (the reversible hydrogen electrode) in the acidic sodium chloride solution (pH 2.3) under one sun illumination. The best-performing photoanode, with 0.05 mol% of Co doping (0.05 Co-BV), selectively produced active chlorine with 92% faradaic efficiency at 1.1 V vs. RHE by successfully suppressing the kinetically sluggish oxygen evolution reaction (OER) and the stability of the catalyst was demonstrated for up to 20 h. This is the lowest operating potential reported for the chlorine evolution reaction (CER), thus far. The overpotential required for CER with 0.05 Co-BV is lower than that of OER, which leads to selective CER at 1.1 V (vs. RHE). Co-doping into the BiVO4 lattice decreases the charge transfer resistance and enhances the CER kinetics due to its structural and electronic integration with the BV lattice. We demonstrate that Co-doping also improves the lifetime of the charge carrier and enhances the current density of CER and sustainability of the catalyst.

Aqueous glycerol to glyceric acid and green hydrogen by visible-light-driven photocatalysis with Ni/Co(PO4)2-TiO2: parallel utilization of holes and electrons - Nivedhitha, Thazhath R.; Bajpai, Himanshu; Oommen, Jiffin Varghese; Abraham, Athira; Chauhan, Inderjeet; Gopinath, Chinnakonda S. (ACS Sustainable Chemistry & Engineering, 2024)
Replacing the kinetically sluggish oxygen evolution reaction (OER) with the oxidation of an abundantly available organic molecule to value-added product(s) (VAPs) at low voltage along with the hydrogen evolution reaction (HER) is a big challenge in water splitting, either by electrolysis or sunlight-driven photocatalysis. Glycerol oxidation to a VAP is kinetically fast, compared to an OER, and offers hope to enhance sunlight-driven water splitting to hydrogen by the concurrent utilization of holes and electrons. Mixed bimetal phosphates of Co and Ni (CoxNiy(PO4)(2) (CoNiP)) with different Co:Ni ratios (10:0, 7:3, 5:5, 3:7, and 0:10) were integrated with TiO2 to generate final photocatalyst composites (x wt % CoNiP with TiO2) and employed for concurrent photocatalytic HER and glycerol oxidation. Irrespective of the weight ratios of CoNiP and TiO2, any TiO2-CoNiP composite showed better photocatalytic activity for the HER and glycerol oxidation compared to virgin TiO2. The highest HER as well as selectively generated glyceric acid yield was observed to be 54 and 67 mmol/g, respectively, after 25 h of reaction under 1 sun conditions with TiO2-CoNiP-5:5. An increase in catalytic activity can be attributed to the formation of p-n heterojunctions of the constituent component along with uniform distribution of CoNiP to effectively utilize the charge carriers for redox reactions. Highly selective oxidation of glycerol to glyceric acid (85%), along with other minor products, is also demonstrated, which offers further scope to use solar light to generate VAPs in a sustainable manner. A simple comparison of H-2 yield and all oxidized products together indicates the better utilization of holes for the latter, and hence, there is scope to increase HER and possibly the whole photocatalytic activity.
Keywords: biomass component; earth-abundantmaterial; energy conversion; organicvalorisation; water splitting

Design of Bi-functional mixed oxide electrodes for selective oxidative C-C cleavage of glycerol to formate and synchronized green hydrogen production - Saha, Arindam; Murugiah, Vasantharadevi; Ranjan, Ravi; Chauhan, Inderjeet; Patra, Kshirodra Kumar; Bajpai, Himanshu; Saha, Avisekh; Gopinath, Chinnakonda S. (Sustainable Energy & Fuels, 2024)
Alkaline water electrolysis is a mature method to produce green hydrogen; however, it suffers from significantly high cost as high overpotentials are required for the oxygen evolution reaction (OER). However, the OER could be avoided altogether by replacing it with kinetically favorable oxidation of abundantly available feedstock molecules at a significantly low potential to value-added product(s) together with green hydrogen generation. This is a potential method to address the high cost of green hydrogen production while converting waste to wealth. Herein, we report green, template-free hydrothermal synthesis of an electrochemically active NiCoMn mixed oxide (NCMO) electrocatalyst with multiple sites, porous structure, large surface area, and nanoneedle (NN) morphology deposited directly over Ni foam (NF). Sustainable electrocatalytic performance was demonstrated for 120 h in 0.2 M alkaline glycerol using chronoamperometry and chronopotentiometry. Highly selective formate production demonstrated an exclusive C-C cleavage with the present catalyst system. Oxides of individual metal-ions (Ni, Co, and Mn) and their bimetallic combination (NiCo, NiMn, and CoMn) exhibited lower activity and product selectivity than the trimetallic NCMO electrocatalyst. The membrane-free two-electrode electrolyzer setup with NCMO/NF at both the anode and cathode (NCMO/NF & Vert;NCMO/NF) requires 1.63 V to accomplish 100 mA cm-2 with 0.2 M glycerol, which is 296 mV less than that of 1 M KOH solution. High faradaic efficiency was observed for hydrogen (98%) with highly selective formate (90%) production. Electrocatalytic formate generation from an alkaline glycerol solution with NCMO is an energy-efficient and promising approach that also supplies carbon-negative green H2. NiCoMn oxide nanoneedles with a cactus-like morphology are shown as bifunctional electrocatalysts that selectively oxidize glycerol to HCOOH and concurrently produce H2.

Electrocatalytic and selective oxidation of glycerol to formate on 2D 3d-metal phosphate nanosheets and carbon-negative hydrogen generation - Chauhan, Inderjeet; Vijay, Pothoppurathu M.; Ranjan, Ravi; Patra, Kshirodra Kumar; Gopinath, Chinnakonda S. (ACS Materials Au, 2024)
In the landscape of green hydrogen production, alkaline water electrolysis is a well-established, yet not-so-cost-effective, technique due to the high overpotential requirement for the oxygen evolution reaction (OER). A low-voltage approach is proposed to overcome not only the OER challenge by favorably oxidizing abundant feedstock molecules with an earth-abundant catalyst but also to reduce the energy input required for hydrogen production. This alternative process not only generates carbon-negative green H2 but also yields concurrent value-added products (VAPs), thereby maximizing economic advantages and transforming waste into valuable resources. The essence of this study lies in a novel electrocatalyst material. In the present study, unique and two-dimensional (2D) ultrathin nanosheet phosphates featuring first-row transition metals are synthesized by a one-step solvothermal method, and evaluated for the electrocatalytic glycerol oxidation reaction (GLYOR) in an alkaline medium and simultaneous H2 production. Co3(PO4)2 (CoP), Cu3(PO4)2 (CuP), and Ni3(PO4)2 (NiP) exhibit 2D sheet morphologies, while FePO4 (FeP) displays an entirely different snowflake-like morphology. The 2D nanosheet morphology provides a large surface area and a high density of active sites. As a GLYOR catalyst, CoP ultrathin (∼5 nm) nanosheets exhibit remarkably low onset potential at 1.12 V (vs RHE), outperforming that of NiP, FeP, and CuP around 1.25 V (vs RHE). CoP displays 82% selective formate production, indicating a superior capacity for C–C cleavage and concurrent oxidation; this property could be utilized to valorize larger molecules. CoP also exhibits highly sustainable electrochemical stability for a continuous 200 h GLYOR operation, yielding 6.5 L of H2 production with a 4 cm2 electrode and 98 ± 0.5% Faradaic efficiency. The present study advances our understanding of efficient GLYOR catalysts and underscores the potential of sustainable and economically viable green hydrogen production methodologies.

Electrocatalytic glycerol conversion: a low-voltage pathway to efficient carbon-negative green hydrogen and value-added chemical production - Chauhan, Inderjeet; Bajpai, Himanshu; Ray, Bishakha; Kolekar, Sadhu K.; Datar, Suwarna; Patra, Kshirodra Kumar; Gopinath, Chinnakonda S. (ACS Applied Materials and Interfaces, 2024)
Electrochemical glycerol oxidation reaction (GLYOR) could be a promising way to use the abundantly available glycerol for production of value-added chemicals and fuels. Completely avoiding the oxygen evolution reaction (OER) with GLYOR is an evolving strategy to reduce the overall cell potential and generate value-added chemicals and fuels on both the anode and cathode. We demonstrate the morphology-controlled palladium nanocrystals, afforded by colloidal chemistry, and their established morphology-dependent GLYOR performance. Although it is known that controlling the morphology of an electrocatalyst can modulate the activity and selectivity of the products, still it is a relatively underexplored area for many reactions, including GLYOR. Among nanocube (Pd-NC), truncated octahedron (Pd-TO), spherical and polycrystalline (Pd-PC) morphologies, the Pd-NC electrocatalyst deposited on a Ni foam exhibits the highest glycerol conversion (85%) along with 42% glyceric acid selectivity at a low applied potential of 0.6 V (vs reversible hydrogen electrode (RHE)) in 0.1 M glycerol and 1 M KOH at ambient temperature. Owing to the much favorable thermodynamics of GLYOR on the Pd-NC surface, the assembled electrolyzer requires an electricity input of only similar to 3.7 kWh/m(3) of H-2 at a current density of 100 mA/cm(2), in contrast to the requirement of >= 5 kWh/m(3) of H-2 with an alkaline/PEM electrolyzer. Sustainability has been successfully demonstrated at 10 and 50 mA/cm(2) and up to 120 h with GLYOR in water and simulated seawater.
Keywords: electrocatalysis; Glycerol; green hydrogen; nanocube; Palladium; SDG

Enhanced electrocatalytic performances of NiCr layered double hydroxides by oxalate intercalation in anion exchange membrane water electrolysis - Pal, Santanu; Sinha, Nibedita; Das, Chandni; Chauhan, Inderjeet; Ahmed, Tanbir; Roy, Poulomi (ACS Applied Materials & Interfaces, 2025)
Layered double hydroxides (LDHs) have attracted much attention these days in the field of water electrolysis due to easy modulation in their layered structure and properties. Herein, NiCr-LDH has been developed, and its interlayer spacing has been considerably increased by oxalate intercalation. Such increased interlayer spacing allows easy access of hydroxides to a large number of electroactive sites and thereby boosts the electrocatalytic performances both for oxygen and hydrogen evolution reactions. Being very active toward both the electrocatalytic reactions, the oxalate-intercalated NiCr-LDH was further explored in an alkaline anion exchange membrane water electrolyzer (AEMWE), achieving 800 mA cm-2 at 1.88 V cell voltage at an operating temperature of 60 degrees C. In fact, the electrolyzer efficiency has been determined to be as high as 69.66%, and the calculated H2 production cost was found to be \$0.97 per gasoline-gallon equivalent, which is well below the targeted cost by the Department of Energy, USA. The electrocatalyst was also examined in harsh alkaline media, like highly saline or seawater, which also indicated its ability to carry out sustainable seawater electrolysis, restricting chlorides to a great extent. Interestingly, post-electrolysis characterization reveals the fact that oxalate decomposition aided carbonate formation within interlayers of NiCr-LDH, and high affinity toward hydroxides is responsible for restricting chlorides during the electrolysis process, apart from the great electrocatalytic activity.
Keywords: Anion exchange; hydrogen production; interlayerspacing; Layered double hydroxide; Sustainable; water electrolyzer

Self-supported super-hydrophilic interconnected nanospikes and particles of MoS2-Ni3S2/NF with optimum d-band center for anion exchange membrane water electrolyzer - Kumar, Yogesh; Barik, Sidharth; Samudre, Nikhil S.; Kharabe, Geeta Pandurang; Chauhan, Inderjeet; Manna, Narugopal; Bhat, Suresh; Kurungot, Sreekumar (Advanced Sustainable Systems, 2025)
There is an imperative need for highly efficient electrocatalysts for cost-effective hydrogen production. Herein, a self-supported, hybrid composite as a bifunctional electrocatalyst is introduced. This is achieved by in situ growth of MoS2-Ni3S2 on nickel foam (NF), designated as MoS2-Ni3S2/NF, synthesized by a facile one-step hydrothermal synthesis method. MoS2-Ni3S2/NF exhibits low overpotentials of only 187 and 146 mV for OER and HER, respectively, to achieve a current density of 10 mA cm-2 in 1 M KOH. The practical application of the designed bifunctional electrocatalyst is verified by constructing the MoS2-Ni3S2/NF || MoS2-Ni3S2/NF symmetrical membrane electrode assembly (MEA) of 4 cm2 working area for the anion exchange membrane water electrolyzer. The system shows continuous electrolysis for the monitored 48 h duration. For OER, an optimum d-band center of -1.66 eV for the heterostructure is calculated from the Density Functional Theory (DFT) studies. The factors like the unique structure of the electrocatalyst, enhanced hydrophilicity, improved electrochemically accessible number of sites (ECASs), and optimum d-band center, are expected to be the primary contributors to the system's improved performance. Thus, the present finding unveils a straightforward synthesis approach for creating a stable electrocatalyst for advancing commercial water electrolysis in the realm of renewable electrochemical energy conversion.
Keywords: AEM; d-band center; electrolyzer; HER; OER

Field emission performance of 2D Ti2CT x (T x = O2, F2, O-F) MXene: experimental insights and theoretical endorsement - Kakade, Prashant M.; Aher, Rahul; Kachere, Avinash R.; Cho, Jinill; Deore, Amol; Jadkar, Sandesh R.; Chauhan, Inderjeet; Kim, Taesung; Mandlik, Nandkumar T.; Kim, Ji Man; Bulakhe, Ravindra N. (ACS Applied Nano Materials, 2026)
Field emission (FE) is an important electron emission mechanism for vacuum microelectronic devices; however, conventional emitters often exhibit high turn-on fields, limited emission stability, and degradation during prolonged operation. Two-dimensional MXenes have recently emerged as promising FE materials due to their remarkable electrical conductivity, comparatively low work function, and tunnelable surface terminations. Nevertheless, most studies have focused on Ti3C2T x MXene, while other compositions such as Ti2CT x remain largely unexplored, particularly regarding the influence of surface terminal groups on their electronic and emission properties. Herein, Ti2CT x (T x = -F2, -O2, -OF) MXene was synthesized via selective chemical etching of the Ti2AlC MAX phase and investigated for its FE characteristics. The material exhibits a polycrystalline hexagonal layered structure with a high specific surface area of 349.02 m2 g-1. Ti2CT x MXene demonstrates excellent FE performance with a low turn-on field of 1.56 V mu m-1 and a threshold field of 2.0 V mu m-1 (at 10 mu A cm-2), along with a stable emission for 4 h. Density functional theory calculations further reveal that surface terminations strongly influence the electronic structure and work function, with the experimental value of 4.66 eV closely matching the -F2 termination. These results highlight Ti2CT x MXene as a promising material for stable and efficient FE applications.
Keywords: 2D Ti2CT x MXene; field emission; TDOS and PDOS; Turn-on voltage; Work function

Potential tuneable glucose oxidation to selective C6 molecules and CC cleavage, and parallel green H2 production: sustainable high current density electrolysis - Chauhan, Inderjeet; Patra, Kshirodra Kumar; Vijay, Pothoppurathu M.; Nalajala, Naresh; Mehta, Shweta; Joshi, Kavita; Ravindranathan, Sapna; Gopinath, Chinnakonda S. (Chemical Engineering Journal, 2026)
Current study elucidates the electrocatalytic efficacy of palladium-nanocubes (Pd-NCs) for the selective oxidation of glucose to value-added chemicals with concomitant hydrogen evolution. The Pd-NC catalyst demonstrated exceptional activity and product selectivity, achieving nearly quantitative glucose conversion (>99 %) with high gluconic and glucaric acid yield at low anodic overpotential (0.6 V vs. RHE) in alkaline electrolyte. At not-so-high elevated potentials (1.2 V vs. RHE), oxidative CC scission prevails, yielding shorter-chain carboxylates along with C6-acids. Reaction products are thoroughly characterized and quantitatively estimated by NMR spectral methods; NMR methods also provide CC cleavage and mechanistic pathways of glucose to various products. Complementary DFT calculations delineate the thermodynamic favorability of glucose adsorption on Pd-NC surfaces (-1.83 eV) and the exergonic oxidation pathway under applied bias, corroborating experimental product distributions. In a two-electrode electrolyzer, Pd-NC anode paired with Pt/C and Ni2P cathode demonstrates 100 mA/cm(2) at 0.99 V and 1.37 V, respectively, with 48 % reduction in energy input (26.6 kWh/kg H-2) compared to conventional alkaline electrolysis; critically, H-2 production energy is lower than the usable energy (33.3 kWh/kg H-2). Sustainable chronopotentiometric assays confirm sustainability (similar to 140 h) in alkaline as well as saline electrolytes, underscoring the system's resilience against chloride-mediated corrosion. Present work establishes a proof of concept for integrated biomass-component valorization and carbon-negative green hydrogen production, merging atomic-level mechanistic insights with scalable reactor design. Optimization of reaction parameters, including potential tuning, reaction temperature and electrolyte engineering, offers a compelling strategy to further enhance C6 and fragmented product selectivity and overall system efficiency.
Keywords: biomass valorization; electrocatalysis; energy conversion; Sustainability